Kesenjangan Implementasi Nilai-Nilai Pancasila Dalam Kehidupan Berbangsa Di Era Digital - Ahmad Fadhilah Anwar (CV. SINAR HOWUHOWU, 2025)
This article examines the gap between the philosophical values of Pancasila as the normative foundation of national life and the realities of social practices in the digital era. Using a critical and interpretive philosophical approach, this study analyzes how the logic of digital spaces—driven by algorithms, virality, anonymity, and fragmented identities—structurally contradicts the holistic, dialogical, and collective principles embedded in the five pillars of Pancasila. Data were collected through a literature review of APJII reports (2025), Kompas Research and Development surveys (2025), academic journals, and documented cases of value violations on social media. The findings reveal systematic distortions of all five principles of Pancasila, particularly in the form of digital dehumanization, algorithmic polarization, and the commodification of religious symbols. The article argues that technocratic solutions alone are insufficient without revitalizing Pancasila as a digital ethos—a practical ethical framework that internalizes the values of humanity, unity, and social justice in every online interaction.